Gambaran Motivasi pada Wirausahawan Muda yang Mengalami Fatherless - Dewi, Eka Puspita; Rahmi, Tuti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the motivation of young entrepreneurs experiencing fatherlessness, namely the physical and psychological absence of a father in their child's life. This study uses a qualitative approach with a narrative-biographical method to understand the subject's life experiences in depth. The subject of the study was a young entrepreneur experiencing fatherlessness, with additional informants from the immediate family. Data collection techniques were carried out through in-depth semi-structured interviews, then analyzed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the subject's motivation is formed through intrinsic and extrinsic motivation. Intrinsic motivation arises from the desire to improve the family's economic condition, achieve a better life, and become an independent individual. Meanwhile, extrinsic motivation is influenced by family support, the social environment, and work experience. The subject's fatherlessness is characterized by minimal attention, the absence of a father's role, and experiences of verbal and physical violence that result in trauma and low emotional closeness. However, the subject is able to build resilience so that these experiences actually become a driving force in achieving entrepreneurial success. This research shows that negative family experiences do not always have a destructive impact, but can be a source of motivation in achieving life goals